Podnebna odpornost – kaj, kako in zakaj? - Kralj, Erik (Revija za geografijo, 2024)
Climate resilience is a key concept in tackling climate change. Definitions of resilience vary according to context and field, but the common denominator is the ability of systems to cope with threats, maintain basic functions and adapt to changes. It is a highly complex concept, as climate resilience requires adaptation of social, economic and environmental systems that are interconnected, and mistakes can quickly be compounded, causing more harm than good. Just as the threats to systems differ, so do the approaches to building climate resilience. Despite the availability of scientific solutions, challenges arise from complexity of systems, conflicting interests, and the need for effective international cooperation. Successful adaptation is key to a sustainable future on a warming planet.
Keywords: adaptation; climate changes; climate resilence; climate threats; podnebna odpornost; podnebne grožnje; podnebne spremembe; prilagajanje; sustainable future; trajnostna prihodnost